90 Improving the Diagnosis of Hymenoptera Venom Allergy: Component Resolved Diagnosis - Cifuentes, Liliana (World Allergy Organization Journal, 2012)
BACKGROUND: Up to 3% of the general population suffers from potentially life-threatening systemic reactions after honeybee and wasp stings. Unfortunately, there are still individuals who have a convincing history of an anaphylactic event, but lack the necessary diagnostic, making difficult the decision for immunotherapy. Our aims were to evaluate the feasibility of using recombinant allergens in the Basophil activation test (BAT) for the diagnosis of Hymenoptera allergy and to develop a high-throughput diagnostic device combining the advantages of basophil activation tests with a panel of recombinant allergens: rVes v 1, rVes v 2, rVes v 3, rVes v 5, rApi m 1, rApi m 2, rApi m 3 and rApi m 5. METHODS: Basophil activation test (BAT) and measurement of specific IgE was performed on 47 wasp venom, 14 Honeybee venom allergic patients and 17 healthy controls. Specificity and sensitivity of BAT performed with recombinant His-tag purified wasp venom allergens Ves v 1, Ves v 2, Ves v 3 and Ves v 5, recombinant honeybee venom allergens Api m 1, Api m 2, Api m 3 and Api m 5 and commercial extracts have been compared. Each patient had a history of grade I or II anaphylaxis after an insect sting. All patient sera were collected before initiation of SIT. RESULTS: BAT performed with the panel of recombinant allergens markedly increased the specificity and the sensitivity in the detection of wasp venom allergic subjects. CONCLUSIONS: Basophil activation test provides a valuable new in vitro method for the detection of allergy to wasp venom and may supplement routine tests for allergy diagnosis in problematic cases. Recombinant allergens might help to dissect relevant allergens for basophil degranulation.